2021
DOI: 10.1177/17470218211009772
|View full text |Cite
|
Sign up to set email alerts
|

Self-referential false associations: A self-enhanced constructive effect for verbal but not pictorial stimuli

Abstract: Memory is considered to be a flexible and reconstructive system. However, there is little experimental evidence demonstrating how associations are falsely constructed in memory and even less is known about the role of the self in memory construction. We investigated whether false associations involving non-presented stimuli can be constructed in episodic memory and if the self plays a role in such memory construction. In two experiments, we paired participants’ own names (i.e., self-reference) or the name “Ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…and answered by participants from the first person perspective (e.g., "No, my parents were not at dinner that evening."). Such self-referenced information is better remembered than other-referenced information, an effect known as the self-reference effect (Symons & Johnson, 1997;Wang et al, 2019Wang et al, , 2021. This might explain why we failed to replicate DIF from a victim perspective.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…and answered by participants from the first person perspective (e.g., "No, my parents were not at dinner that evening."). Such self-referenced information is better remembered than other-referenced information, an effect known as the self-reference effect (Symons & Johnson, 1997;Wang et al, 2019Wang et al, , 2021. This might explain why we failed to replicate DIF from a victim perspective.…”
Section: Discussionmentioning
confidence: 92%
“…This might be especially true for the interview in which questions were asked from the second person perspective (e.g., “Did your parents go with you to dinner that evening?”) and answered by participants from the first person perspective (e.g., “No, my parents were not at dinner that evening.”). Such self‐referenced information is better remembered than other‐referenced information, an effect known as the self‐reference effect (Symons & Johnson, 1997; Wang et al., 2019, 2021). This might explain why we failed to replicate DIF from a victim perspective.…”
Section: Discussionmentioning
confidence: 99%
“…For example, after children saw objects paired with their own images or others' images, they remembered more stimuli-self associations than stimuli-other associations (Cunningham, Brebner, Quinn, & Turk, 2014). Our recent study also found that young adults showed higher stimuli-self associative memories than stimuli-other associative memories (Wang, Otgaar, Howe, & Cheng, 2021).…”
Section: Self-enhanced False Memory Across the Life Spanmentioning
confidence: 52%
“…Research found that self-reference increased the false recollection of critical lures but not familiarity in younger adults (Ozdes et al, 2021;Wang et al, 2021). That is, selfreferencing boosts the phantom recollection of "seeing" critical lures.…”
Section: Self-enhanced False Memory Across the Life Spanmentioning
confidence: 95%
See 1 more Smart Citation